WALNUTS for POWER: A Protocol for the Polyphenols, Omega-3 Fatty Acids, Weight Loss, and EneRgy Randomized Controlled Trial. (29th May 2020) - Csizmadi, Ilona; Lin, Pao-Hwa; Freeman, Michael; Knudsen, Beatrice; Rogatko, Andre; Devkota, Suzanne; You, Sungyong; Jarman, Aubrey; Lockshon, Laura; Tan, Anamarie; Daskivich, Timothy; Desai, Premal; et al.
Abstract: Objectives: Prostate cancer (PC) is the most common non-skin cancer in men and the second leading cause of cancer death. Omega-3 fatty acids and polyphenols have bioactive properties that may alter tumor biology and reduce PC progression. Walnuts (Juglans regia L.) are one of the best sources of plant-based omega-3 s (2.5 g per oz) and polyphenols (total polyphenols 462 mg per oz). We propose to determine the effect of walnuts added to a typical diet on markers of PC progression in men scheduled for radical prostatectomy (RP). The primary objective of the study is to determine the effect of walnut intake on Ki67 expression in prostatic tissue. Secondary objectives are to determine the effect of walnuts on prostatic tissue oxidative stress and inflammation. Exploratory objectives include measuring the effect of walnuts on the gut microbiome, insulin/IGF signaling and gene expression. Methods: 50 men with PC scheduled for RP are recruited from the Durham Veterans Medical Center and Cedars-Sinai Medical Center. Men are randomized to receive 2 oz. of walnuts added to a usual diet (intervention) or control (usual diet) using a 1:1 allocation during the 3–10-week pre-RP period. An experienced dietitian provides counseling and recipes to men in the intervention arm and monitor dietary compliance. RP tissue is stained and scored for Ki67 by an experienced pathologist. Tumors are processed for RNA extraction and RNA-sequenced at the UCLA genomics core. Fasting blood are collected at baseline and pre-RP visits, spun, separated into serum, plasma, and red blood cells and stored at −80°C. Serum are batch-analyzed for insulin, IGF-1, IGFBP-3, and IL-6. Stool samples for microbiota analyses are collected at baseline and pre-RP visits and undergo 16 s rRNA gene sequencing and statistical analyses to identify microbiome community content. Between-arm differences during the study are assessed by t-test for continuous variables and chi-square test for categorical variables. The study will be completed in 3 years. To date, 7 men have been recruited. Results: N/A Conclusions: If shown to be effective in improving PC outcomes in men diagnosed with early stage PC, this modest dietary change could provide a much needed feasible, low-cost, easily accessible, non-toxic option that could be sustained over the long-term. Funding Sources: California Walnut Commission.